A Genome-Wide Functional Genomics Approach Identifies Susceptibility Pathways to Fungal Bloodstream Infection in Humans. (24th April 2019) - Jaeger, Martin; Matzaraki, Vasiliki; Aguirre-Gamboa, Raúl; Gresnigt, Mark S; Chu, Xiaojing; Johnson, Melissa D; Oosting, Marije; Smeekens, Sanne P; Withoff, Sebo; Jonkers, Iris; Perfect, John R; van de Veerdonk, Frank L; et al.
Abstract: Background: Candidemia, one of the most common causes of fungal bloodstream infection, leads to mortality rates up to 40% in affected patients. Understanding genetic mechanisms for differential susceptibility to candidemia may aid in designing host-directed therapies. Methods: We performed the first genome-wide association study on candidemia, and we integrated these data with variants that affect cytokines in different cellular systems stimulated with Candida albicans . Results: We observed strong association between candidemia and a variant, rs8028958, that significantly affects the expression levels of PLA2G4B in blood. We found that up to 35% of the susceptibility loci affect in vitro cytokine production in response to Candida . Furthermore, potential causal genes located within these loci are enriched for lipid and arachidonic acid metabolism. Using an independent cohort, we also showed that the numbers of risk alleles at these loci are negatively correlated with reactive oxygen species and interleukin-6 levels in response to Candida . Finally, there was a significant correlation between susceptibility and allelic scores based on 16 independent candidemia-associated single-nucleotide polymorphisms that affect monocyte-derived cytokines, but not with T cell-derived cytokines. Conclusions: Our results prioritize the disturbed lipid homeostasis and oxidative stress as potential mechanisms that affect monocyte-derived cytokines to influence susceptibility to candidemia. Abstract : Understanding genetic mechanisms for candidemia susceptibility may help designing host-directed therapies. By performing the first candidemia GWAS and in vitro stimulation experiments using population-based cohorts, we prioritized lipid homeostasis and oxidative stress as potential susceptibility mechanisms that affect Candida -response cytokines.